Evidence-based citation analysis of a health sciences journal collection. - Meschino, Madeline; Naik, Gauri; Lipke, Laura (Medical Reference Services Quarterly)
This study demonstrates how health sciences librarians can use citation analysis, COUNTER statistics, and interlibrary loan data to quantitatively evaluate journal collections across multiple health sciences programs. Unlike previous studies focusing on single professions, this research analyzed an entire health sciences college collectively. Results showed 90.5-100% of journals used by faculty for publication and citation were available in the library's catalog, validating the collection's value. These findings provide a framework for collection development, resource promotion, and budget justification. The methodology is particularly valuable for librarians managing collections serving multiple programs within health sciences institutions.